Atividades didáticas de física na formação inicial de professores de biologia - Gonçalves, Aline (2019)
The current masters degree research presented to course Pós-Graduação em Educação em Ciências: Química da Vida e Saúde, of Universidade Federal de Santa Maria (UFSM, RS), has constituted in investigating the feasibility of a set didactic activities (DAs) as tools in the Physics classes in Biological Sciences Undergraduate Course of Universidade Federal de Santa Maria - campus located in Palmeira das Missões/RS. In this perspective, we developed, implemented, and evaluated five DAs - based on Information and Communication Technologies (ICT). We considered the ICT resources, by itself, not produce changes in teaching and learning process, therefore, the investigative activities arise with a possible alternative to enhance and make more flexible the learning, becoming each student the process active subject. We proposed the following research problem: What is the application feasibility of a DAs set, using computational simulations (CS) as an investigative way to physics phenomena study in Biological Sciences Undergraduate Course? With the purpose of answering this problem, we use, to guide our work, the research conception based on methodology Education Design Research (EDR). In practice, the EDR seeks to identify a real problem in concrete contexts of teaching and learning and, once the problem is drawn, it purposes the scientific investigation development, searching for a possible solution. In our study, the referral was through DAs developed, implemented in extra class activities, by the students and evaluated in online portal gxq. The results pointed out in this survey indicate that DAs sequence comply with main objective to investigate the potentialities of such tasks as tools on Physics classes to Biological Sciences course. Starting from the analysis of the initial questionnaire, from digital message contact, from proposed questions analysis, and from individual questionnaire for each activity, we evidence that DAs, present application potentialities and contribute to scientific and technological knowledge in an interdisciplinary perspective.